Early elevation in plasma high-sensitivity troponin T and morbidity after elective noncardiac surgery: prospective multicentre observational cohort study. (May 2020) - ,; ,; ,; ,; Pearse, Rupert; Niebrzegowska, Edyta; Wragg, Andrew; Archbold, Andrew; Kam, Elisa; Everingham, Kirsty; Bodger, Phoebe; Creary, Thais; et al.
Abstract: Background: Elevated high-sensitivity troponin (hsTnT) after noncardiac surgery is associated with higher mortality, but the temporal relationship between early elevated troponin and the later development of noncardiac morbidity remains unclear. Methods: Prospective observational study of patients aged ≥45 yr undergoing major noncardiac surgery at four UK hospitals (two masked to hsTnT). The exposure of interest was early elevated troponin, as defined by hsTnT >99th centile (≥15 ng L −1 ) within 24 h after surgery. The primary outcome was morbidity 72 h after surgery, defined by the Postoperative Morbidity Survey (POMS). Secondary outcomes were time to become morbidity-free and Clavien–Dindo ≥grade 3 complications. Results: Early elevated troponin (median 21 ng L −1 [16–32]) occurred in 992 of 4335 (22.9%) patients undergoing elective noncardiac surgery (mean [standard deviation, sd ] age, 65 [11] yr; 2385 [54.9%] male). Noncardiac morbidity was more frequent in 494/992 (49.8%) patients with early elevated troponin compared with 1127/3343 (33.7%) patients with hsTnT <99th centile (odds ratio [OR]=1.95; 95% confidence interval [CI], 1.69–2.25). Patients with early elevated troponin had a higher risk of proven/suspected infectious morbidity (OR=1.54; 95% CI, 1.24–1.91) and critical care utilisation (OR=2.05; 95% CI, 1.73–2.43). Clavien–Dindo ≥grade 3 complications occurred in 167/992 (16.8%) patients with early elevated troponin, compared with 319/3343 (9.5%) patients with hsTnT <99th centile (OR=1.78; 95% CI, 1.48–2.14). Absence of early elevated troponin was associated with morbidity-free recovery (OR=0.44; 95% CI, 0.39–0.51). Conclusions: Early elevated troponin within 24 h of elective noncardiac surgery precedes the subsequent development of noncardiac organ dysfunction and may help stratify levels of postoperative care in real time.